Long‐term streamflow trends in the middle reaches of the Yellow River Basin: detecting drivers of change. Issue 9 (21st November 2015) - Gao, Zhaoliang; Zhang, Lu; Zhang, Xiaoping; Cheng, Lei; Potter, Nick; Cowan, Tim; Cai, Wenju
Abstract: The catchments in the Loess Plateau, in China's middle reaches of the Yellow River Basin, experienced unprecedented land use changes in the last 50 years as a result of large‐scale soil conservation measure to control soil erosion. The climate of the region also exhibited some levels of change with decreased precipitation and increased temperature. This study combined the time‐trend analysis method with a sensitivity‐based approach and found that annual streamflow in the Loess Plateau decreased significantly since the 1950s and surface runoff trends appear to dominate the streamflow trends in most of the catchments. Annual baseflow exhibited mostly downward trends, but significant upward trends were also observed in 3 out of 38 gauging stations. Mean annual streamflow during 1979−2010 decreased by up to 65% across the catchments compared with the period of 1957−1978, indicating significant changes in the hydrological regime of the Loess Plateau. It is estimated that 70% of the streamflow reduction can be attributed to land use change, while the remaining 30% is associated with climate variability. Land use change because of the soil conservation measures and reduction in precipitation are the key drivers for the observed streamflow trends. These findings are consistent with results of previous studies for the region and appear to be reasonable given the accelerated level of the soil conservation measures implemented since the late 1970s. Changes in sea surface temperature in the Pacific Ocean, as indicated by variations in El Niño–Southern Oscillation and phase shifts of the Pacific Decadal Oscillation, appear to have also affected the annual streamflow trends. The framework described in this study shows promising results for quantifying the effects of land use change and climate variability on mean annual streamflow of catchments within the Loess Plateau. Copyright © 2015 John Wiley & Sons, Ltd.